Perancangan Ulang Tata Letak Fasilitas Laboratorium Pabrik Gula Dengan Metode Computerized Relationship Layout Planning(CORELAP) (Studi Kasus PT Kebun Tebu Mas) - Imam Putra Utama; Andhika Mayasari; Sulung Rahmawan Wira Ghani; Minto (INVANTRI (Inovasi Dan Pengelolaan Industri), 2022)
PT Kebun Tebu Mas is a manufacturing company that produces white crystal sugar for the community, and refined sugar for industrial needs. In the sugar manufacturing industry, it is necessary to design the layout of the facility, especially in the laboratory section, it aims to make the work more effective and create an efficient transfer distance of the analysis process, with the hope that quality control can be carried out optimally. The obstacle faced by the laboratory of PT Kebun Tebu Mas is the layout design of the facilities which is not neatly arranged. The purpose of this research is to design an improved layout using the CORELAP method. The laboratory of PT Kebun Tebu Mas has 16 main facilities to analyze 13 core parameters, in quality control. The research was conducted using the CORELAP construction method, where qualitative data will be converted to quantitative data, as a basis and description for designing the layout of the facility. The results of this study are able to minimize the distance of 84 meters, so that the analysis process becomes more effective, where the displacement distance in the initial layout is 206.5 meters while the displacement distance in the improved layout is 122.5 meters, so that distance efficiency is 40.7% and time efficiency is 55. ,24%.